Analisis Perhitungan Harga Pokok Produksi Menggunakan Activity-Based Costing System Dalam Menentukan Harga Jual - Ayu Uswatun Hasanah; Suji Abdullah Saleh (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The company is expected to be able to face business competition among the company's competitors by achieving profit targets by the company. The purpose of this study is to compare the calculation of the cost of production using the traditional costing method and the ABC system in increasing the accuracy for determining the selling price. This type of research is descriptive quantitative. The types of data used are subject and documentary data. This research requires primary data sources. Data collection techniques using interviews, observation, and documentation. The data analysis technique uses the ABC System to calculate the cost of goods manufactured and the selling price formula. The results of this study, there is a cost distortion in traditional costing. The traditional costing factory overhead is allocated using one cost driver, while the ABC System is assigned several cost drivers. With the ABC System, cost components can be allocated to products appropriately based on their use.